2019
DOI: 10.1371/journal.pone.0219144
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and lipid outcomes in children and adolescents with type 2 diabetes

Abstract: Background The incidence of type 2 diabetes (T2DM) in children has increased dramatically. However, limited published information is known about the glycemic control and lipid outcomes in pediatric T2DM outside of clinical trials. Objectives To determine the glycemic control and lipid measure outcomes at one and three- year follow-up in children with T2DM. Methods A retrospective electronic medical record review of children with T2DM at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…More than half of the T2D patients failed to achieve the glycemic target after 5 years, comparable with previous studies 23 , 24 . Several studies have evaluated real-world longitudinal trends in the HbA1c level in youth with T2D 23 26 , and reported worsening of glycemic control from 1 to 1.5 years after diagnosis 25 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…More than half of the T2D patients failed to achieve the glycemic target after 5 years, comparable with previous studies 23 , 24 . Several studies have evaluated real-world longitudinal trends in the HbA1c level in youth with T2D 23 26 , and reported worsening of glycemic control from 1 to 1.5 years after diagnosis 25 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…A phase 2 trial of IONIS-ANGPTL3-L Rx (this acts primarily within hepatocytes to block production of hepatic ANGPTL3) in patients with T2D, hepatosteatosis, and TG > 200 mg/dL is underway (NCT03371355) in adults. Some of the ongoing clinical trials aim to test newer medications whose primary outcome is improving glycemic control in pediatric patients, with dyslipidemia being studied as a secondary outcome of the study get another ongoing studies include clinical trials on the safety and efficacy of ertugliflosin, an SGLT-2 inhibitor (NCT04029480), a [82,83] ↓ ↑ ↓ Mostly cohort studies with short term data Insulin [52,53,84] ↓ ↑ ↔ Significant when A1C ≤ 8% Metformin [52,53,84,85] ↓ Mild ↑ ↓ TODAY study: 55.9% of the youth remained at the LDL-C goal of < 100 mg/dL over the first 3 years. Levels of TG, apo B, and non-HDL-C rose from baseline to the end of the first year and remained at a higher level for the next 2 years.…”
Section: Ongoing Clinical Studies For Dyslipidemia In T2dmentioning
confidence: 99%
“…Consumption of energy-dense foods in children and teenagers with a family history of type 2 diabetes, plays a central role in the formation of a worse glycemic profile and potentially, subsequent development of type 2 diabetes (T2D) [ 16 ]. T2D in children is associated with a deteriorated lipidemic profile (i.e., dyslipidemia), as a direct effect of the observed insulin resistance [ 17 ]. A different study showed that Greek children with dyslipidemia and unfavourable dietary habits, such as consuming only one meal per day, displayed higher levels of various biomarkers of lipidemic control, namely total cholesterol and low-density lipoprotein cholesterol (LDL-C) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%